Canadian Consensus Guidelines for the Optimal Use of Maraviroc in the Treatment of HIV-Infected Adults - Anita Rachlis; Marianne Harris; Richard Lalonde; Stephen D Shafran; Cécile Tremblay; Mark A Wainberg; Sharon Walmsley (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND AND OBJECTIVES: A Canadian group, consisting of six physicians and an HIV researcher with significant experience and knowledge in HIV management, reviewed the available data and developed guidelines for Canadian health care providers (who treat HIV infection) on the appropriate use of maraviroc (UK-427,857) in HIV-infected adults.